Psychiatry trainees' views and educational needs regarding the care of patients with a life-limiting illness. Issue 2 (20th June 2016) - Forster, Benjamin C.; Proskurin, Helen; Kelly, Brian; Lovell, Melanie R.; Ilchef, Ralf; Clayton, Josephine M.
Abstract: Objective: People with a life-limiting physical illness experience high rates of significant psychological and psychiatric morbidity. Nevertheless, psychiatrists often report feeling ill-equipped to respond to the psychiatric needs of this population. Our aim was to explore psychiatry trainees' views and educational needs regarding the care of patients with a life-limiting physical illness. Method: Using semistructured interviews, participants' opinions were sought on the role of psychiatrists in the care of patients with a life-limiting illness and their caregivers, the challenges faced within the role, and the educational needs involved in providing care for these patients. Interviews were audiotaped, fully transcribed, and then subjected to thematic analysis. Results: A total of 17 psychiatry trainees were recruited through two large psychiatry training networks in New South Wales, Australia. There were contrasting views on the role of psychiatry in life-limiting illness. Some reported that a humanistic, supportive approach including elements of psychotherapy was helpful, even in the absence of a recognizable mental disorder. Those who reported a more biological and clinical stance (with a reliance on pharmacotherapy) tended to have a nihilistic view of psychiatric intervention in this setting. Trainees generally felt ill-prepared to talk to dying patients and felt there was an educational "famine" in this area of psychiatry. They expressed a desire for more training and thought that increased mentorship and case-based learning, including input from palliative care clinicians, would be most helpful. Significance of Results: Participants generally feel unprepared to care for patients with a life-limiting physical illness and have contrasting views on the role of psychiatry in this setting. Targeted education is required for psychiatry trainees in order to equip them to care for these patients.